Effect of metformin in addition to an antenatal diet and lifestyle intervention on fetal growth and adiposity: the GRoW randomised trial - Poprzeczny, Amanda J. (BMC Endocr Disord, 2020)
BACKGROUND: The infants born to women who are overweight or obese in pregnancy are at an increased risk of being born macrosomic or large for gestational age. Antenatal dietary and lifestyle interventions have been shown to be ineffective at reducing this risk. Our aim was to examine the effects of metformin in addition to a diet and lifestyle intervention on fetal growth and adiposity among women with a BMI above the healthy range. METHODS: Women who had a body mass index ≥25 kg/m(2) in early pregnancy, and a singleton gestation, were enrolled in the GRoW trial from three public maternity hospitals in metropolitan Adelaide. Women were invited to have a research ultrasounds at 28 and 36 weeks’ gestation at which ultrasound measures of fetal biometry and adiposity were obtained. Fetal biometry z-scores and trajectories were calculated. Measurements and calculations were compared between treatment groups. This secondary analysis was pre-specified. RESULTS: Ultrasound data from 511 women were included in this analysis. The difference in femur length at 36 weeks’ gestation was (0.07 cm, 95% CI 0.01–0.14 cm, p = 0.019) and this was was statistically significant, however the magnitude of effect was small. Differences between treatment groups for all other fetal biometry measures, z-scores, estimated fetal weight, and adiposity measures at 28 and 36 weeks’ gestation were similar. CONCLUSIONS: The addition of metformin to dietary and lifestyle advice in pregnancy for overweight and obese women has no clinically relevant effect on ultrasound measures of fetal biometry or adiposity. TRIAL REGISTRATION: Australian and New Zealand Clinical Trials Registry (ACTRN12612001277831).